Analysis of the Roles of Southern Coastal Road Construction Between Tulungagung and Trenggalek Regencies in Developing the Economy of Tasikmadu and Keboireng Villages - Dewan Dharu, Aditya Gangga; Maryunani (Journal of Development Economic and Social Studies, 2025)
This study aims to identify the sectors that influence the economy in Desa Tasikmadu and Desa Keboireng. Secondly, it seeks to understand the sustainable economic development policies for these villages following the construction of the southern coastal road (JLS). This research uses Partial Least Squares (PLS) analysis, collecting data related to economic variables after the development of the southern coastal road. The analysis results through SEM PLS testing indicate a significant impact of the economic variables with the presence of the southern coastal road development, providing deep insights into the impact of infrastructure development on the local economy. These findings can serve as the basis for better policy recommendations to harness the potential of the southern coastal road development to improve the welfare of the communities in Desa Tasikmadu and Desa Keboireng. The results show that the JLS has increased investment, reduced unemployment, and encouraged consumption, which significantly drives the village economy. Improved accessibility opens up business opportunities, increases community income, and expands local markets. This development also stimulates the growth of the tourism sector and the distribution of local products, supporting sustainable economic growth in both villages.   Abstrak Penelitian ini bertujuan untuk mengetahui sektor apa saja yang mempengaruhi perekonomian di Desa Tasikmadu dan Desa Keboireng. Kedua, mengetahui kebijakan pembangunan perekonomian Desa Tasikmadu dan Desa Keboireng secara berkelanjutan setelah adanya jalan lintas selatan (JLS). Penelitian ini menggunakan metode analisis PLS, kami mengumpulkan data terkait variabel ekonomi sesudah pembangunan jalan lintas selatan. Hasil analisis melalui uji PSL SEM dapat mengindikasikan adanya pengaruh yang signifikan dalam variabel ekonomi dengan adanya pembangunan jalan lintas selatan, memberikan wawasan mendalam tentang dampak pembangunan infrastruktur terhadap perekonomian lokal. Penemuan ini dapat menjadi dasar untuk rekomendasi kebijakan yang lebih baik dalam memanfaatkan potensi pembangunan jalan lintas selatan untuk meningkatkan kesejahteraan masyarakat di Desa Tasikmadu dan Desa Keboireng. Hasilnya menunjukkan bahwa JLS meningkatkan investasi, menurunkan pengangguran, dan mendorong konsumsi, yang secara signifikan mendorong perekonomian desa. Aksesibilitas yang lebih baik membuka peluang usaha, meningkatkan pendapatan masyarakat, dan memperluas pasar lokal. Pembangunan ini juga memicu pengembangan sektor pariwisata dan distribusi produk lokal, mendukung pertumbuhan ekonomi berkelanjutan di kedua desa.